Improved Treatment Of Pyelonephritis In Children During The Covid-19 Pandemic - Gapparova Guli Nurmuminovna; Akhmedjanova Nargiza Ismailovna (Genius Journals, 2023)
The novel coronavirus disease (COVID-19), called severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2), first appeared in Wuhan, China in December 2019 [1, 2, 8 ]. Soon after, the World Health Organization (WHO) declared a global pandemic. The purpose of the work: to evaluate the clinical effectiveness of the use of vitamin A (Retinol amine) in children with pyelonephritis against the background of COVID-19. Materials and research methods: -we selected 100 children as research groups. Group I - Main group, Group II - Control group. All patients were examined using clinical, instrumental and laboratory methods. Clinical-laboratory examination methods of sheep were carried out in them: general blood and urine analysis; bacteriological examination of urine; determination of urea and creatinine in blood, total blood protein, procalcitonin, creatinine in urine, concentration ability of kidneys by Zimnitsky test. Results: according to clinical, laboratory and instrumental examination, children with pyelonephritis were divided into two groups. Child patients in the main group received standard therapy for COVID-19, 50 children in the main group were prescribed ageappropriate vitamin A along with standard therapy for COVID-19. The clinical effectiveness of the treatment was evaluated in dynamics up to 10 days. Children with normal clinical and laboratory parameters were taken for outpatient observation. Conclusions: Our clinical evidence shows that during the COVID-19 pandemic, adding retinol amine to pediatric patients with pyelonephritis significantly improved the clinical outcome of the disease.
Keywords: COVID-19; pyelonephritis; protienuria